Implementing category management of services – a new methodology. Issue 2 (3rd June 2019) - Apte, Aruna; Arruda, Corey; Clark, Austin; Landale, Karen
Abstract : Purpose: In an increasingly budget-constrained environment, the Department of Defense (DoD) must maximize the value of fiscal resources obligated on service contracts. Over half of DoD procurement spending between 2008 and 2012 was obligated on service contracts (GAO, 2013). Many services are common across the enterprise and recurring in nature; however, they are treated as unique and procured individually at the base level, year after year, rather than collectively in accordance with a larger, enterprise-wide category management strategy. The purpose of this paper is to focus on creating a methodology that treats common, recurring service requirements in a more strategic manner. Design/methodology/approach: The authors develop a standardized, repeatable methodology that uses relevant cost drivers to analyze service requirements to identify more efficient procurement strategies. Furthermore, they create a clustering continuum to organize services based on proximity between the customer-supplier bases. This paper uses a commercial business mapping software to analyze cost driver data, produce visualizations and illustrate strategic opportunities for category management initiatives. DoD requirements for Integrated Solid Waste Management (ISWM) within the Los Angeles area are evaluated using the software and methodology to demonstrate a model for practical application. Findings: The authors find that commercial software can be used to cluster requiring activities needing common, recurring services. This standardized, repeatable method can be applied to any category of services with any number of cost drivers. By identifying optimal requiring activity clusters, procurement agencies can more effectively implement category management strategies for service requirements. Research limitations/implications: The initial approach of this paper was to develop a macro-level, one-size-fits-all model to centralize procurement. The authors found this approach inadequate as they tried to group service requirements of wildly differing characteristics. They experienced other significant limiting factors related to data availability and data collection. Social implications: Clustering common and recurring DoD service requirements would result in standardized levels of service at all installations. The demand savings from clustering would promote the implementation of best practices for that service requirement across the DoD, which would eliminate non-value-added activities currently performed at some installations, or gold-plating of requirements, which is also likely occurring. Originality/value: This paper is the first to use an analytics-based methodology to cluster common, recurring public services. It is the first method that offers a standardized, repeatable approach to implementing category management of service requirements to achieve cost savings.